Power intake size optimization for economical hydropower - Satyajeet Sinha (Results in Engineering, 2022)
Power intakes are provided in hydropower projects for hydraulically efficient water inlets to the water passages leading to the powerhouse. The power intake structure comprises of intake entrance, trash racks, and transition. From a detailed study carried out, author's experience of hydropower projects and the relevant analytical results, it is deduced that the power intake can be optimized significantly by reducing the cross-sectional area of its components and the structure can be economized without any significant impact on its performance. In place of the state of art bellmouth equation the author has suggested the alternate equations which gives much reduced entrance profile, trash racks sizing can be decreased by altered orientation along with increased cleaning frequency, and adopting the recommended hydraulic efficient transition section the sizing can be optimized. The list of mega hydropower projects and a case study are discussed for demonstration. These potential cost reductions in equipment and civil structures of hydropower component minimizes the cost of hydropower projects and are a factor in expanding hydropower and keeping it competitively priced in the energy market. For long-term costs and benefits of energy sales, the optimal size power intake suggested in this study can be adopted for million dollars saving.